Nitric oxide-releasing gel accelerates healing in a diabetic murine splinted excisional wound model - Sivaraj, Dharshan; Noishiki, Chikage; Kosaric, Nina; Kiwanuka, Harriet; Kussie, Hudson C.; Henn, Dominic; Fischer, Katharina S.; Trotsyuk, Artem A.; Greco, Autumn H.; Kuehlmann, Britta A.; Quintero, Filiberto; Leeolou, Melissa C.; et al. (Frontiers in Medicine, 2023)
According to the American Diabetes Association (ADA), 9-12 million patients suffer from chronic ulceration each year, costing the healthcare system over USD $25 billion annually. There is a significant unmet need for new and efficacious therapies to accelerate closure of non-healing wounds. Nitric Oxide (NO) levels typically increase rapidly after skin injury in the inflammatory phase and gradually diminish as wound healing progresses. The effect of increased NO concentration on promoting re-epithelization and wound closure has yet to be described in the context of diabetic wound healing. In this study, we investigated the effects of local administration of an NO-releasing gel on excisional wound healing in diabetic mice. The excisional wounds of each mouse received either NO-releasing gel or a control phosphate buffered saline (PBS)-releasing gel treatment twice daily until complete wound closure. Topical administration of NO-gel significantly accelerated the rate of wound healing as compared with PBS-gel treated mice during the later stages of healing. The treatment also promoted a more regenerative ECM architecture resulting in shorter, less dense, and more randomly aligned collagen fibers within the healed scars, similar to that of unwounded skin. Wound healing promoting factors fibronectin, TGF-β1, CD31, and VEGF were significantly elevated in NO vs. PBS-gel treated wounds. The results of this work may have important clinical implications for the management of patients with nonhealing wounds.